Concrete leaching of a hydroelectric powerhouse due to 40 years of exposure to river water. (4th October 2021) - Neumann, C.; Faria, E.F.; dos Santos, A.C.P.
Abstract: This article presents a study on concrete leaching mechanisms due to 40 years of exposure to river water. Many hydropower structures suffer from concrete deterioration by leaching in joints, drains etc., particularly when calcium hydroxide ions are transported to the external environment, resulting in increased porosity, absorption and decreased mechanical properties. The objective of this study is to evaluate the current stage of the leaching process of the backfill concrete of the Itaipu Binacional Hydroelectric Powerhouse foundations. Concrete core samples drilled out at four vertically different locations were analysed by X-ray diffraction, thermogravimetry and scanning electron microscopy. Chemical essays of infiltration water which were carried out over a period of 40 years were studied. Long-term exposure to the flow of soft water, which came from the downstream river has led to chemical and mineralogical alteration in some regions of the backfill concrete. The degradation by leaching has localized effects, limited to the areas of the highest percolation flows. Highlights: A 40-year concrete leaching mechanism analysis. Importance of chemical tests in dam monitoring. Contribution to the knowledge of concretes under long-term leaching. Properties of the concrete placed in powerhouse foundations, subjected to leaching.